MODEL PELAKSANAAN PENDIDIKAN FULL DAY SCHOOL DI MTs NEGERI 1 KOTA SERANG - Fauzi, Anis (EDUKASIA, 2019)
This study aims to understand perceptions of teachers, education personnel, students and parents about full day school education program; basic concepts of full day school education; factors driving or impeding the implementation of full day school education at research site; and follow-up of full day school program in the future. This research used quantitative and qualitative approach with descriptive method and rely on data collection technique from spreading questionnaire, observation, interview, documentation, and literature study. Data analysis techniques used description analysis techniques. The population in this study were teachers who were given additional task as vice principal at State Madrasah Tsanawiyah (MTs) 1 Serang, student and parents in class VIII as representative respondents. Processing and data analysis was done gradually, along with the emergence and development of information input from research subjects. The conclusion of this study is teachers and education personnel of State MTs 1 Serang agreed to implement full day school education program, in order to: prepare themselves to face the era of competition in economic society of ASEAN environment; strengthen the motivation and competition of student learning process; improve work motivation and performance of teachers and administrative staff; also maintaining the establishment of happy and prosperous families by using "Saturday" as a family holiday.